2021
DOI: 10.1590/1980-5373-mr-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Mechanical Attrition Treatment on Micro-mechanical Properties of ZrCuAlNi Bulk Metallic Glass

Abstract: In this work, surface mechanical attrition treatment (SMAT) was employed to rejuvenate ZrCuAlNi bulk metallic glass (BMG) plate. Differential scanning calorimetry (DSC), atomic force microscopy (AFM) and nanoindentation analyses were carried out to evaluate stored energy and micro-mechanical properties of treated BMGs. According to DSC results, 10 min SMAT process increased the stored energy of BMG plates up to 50%. AFM analysis showed that the structural rejuvenation occurred in the bulk of samples and just a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…With comparison of the d max and d f values, it is possible to find out the level of anelastic strain in the Fe-based alloys, which is indicator of loosely packed regions in the glassy structure. [45] The d f /d max ratio in the amorphous alloys reflects the level of anelasticity in the microstructure (see Fig. 4(c)).…”
Section: Methodsmentioning
confidence: 98%
“…With comparison of the d max and d f values, it is possible to find out the level of anelastic strain in the Fe-based alloys, which is indicator of loosely packed regions in the glassy structure. [45] The d f /d max ratio in the amorphous alloys reflects the level of anelasticity in the microstructure (see Fig. 4(c)).…”
Section: Methodsmentioning
confidence: 98%
“…This was identified as a key reason for the saturation of rejuvenation in the MGs. In another work, Shayakhmetov et al [17] showed that an optimized state exists for the rejuvenation under the mechanical attrition treatment, which may be due to the saturation of anelastic strain energy in the body of glassy material. Using the synchrotron x-ray diffraction, it was also found that in highly deformed regions under the highpressure torsion the local mean atomic volume is increased up to about 0.75%, thus achieving a saturated rejuvenated structure.…”
Section: Introductionmentioning
confidence: 99%